Teratoma quístico maduro mediastínico que se presenta como hemoptisis - Pamo-Reyna, Oscar G. (2019)
An 18 year-old woman entered to the hospital because of thoracic pain and dyspnea on exertion in the last nine months, and recurrent hemoptysis. The image studies revealed a mass in the anterior-superior mediastinum. After surgical resection, histopathology showed several epithelial and cartilaginous tissues compatible with mature cystic teratoma.